Awareness Regarding Anemia, Gestational Diabetes and Pregnancy Induced Hypertension Among Antenatal Women Attending Outpatient Department in A Rural Hospital - George, Meera; George, Neethu; Ramesh, Naveen (National Journal of Community Medicine, 2016)
Introduction: Antenatal mothers should be aware about common morbidities like anemia, gestational diabetes mellitus (GDM), pregnancy induced hypertension (PIH), etc., which can have adverse pregnancy outcomes. This study was conducted to assess the awareness regarding anemia, GDM and PIH among antenatal women attending outpatient clinic in a rural hospital. Methods: This was a cross sectional study done during the period of October-November 2014. After obtaining informed consent pre-validated, structured questionnaire was used to assess the awareness about anemia, GDM and PIH among 150 antenatal women attending the outpatient clinic at the rural hospital. Results: A total of 150 antenatal women participated in the study. Majority of respondents (104 -69.3%) were aged 20-25 years, educated 70 (46.7%) and most of them were homemakers 129 (86%). Majority of them 97(64.7%) were primigravida and were from joint family 75 (50%). Among the study participants, most of them 124 (82.67%) had good knowledge regarding anemia, fair knowledge 73 (48.67%) regarding gestational diabetes and good knowledge 94 (62.7%) regarding pregnancy induce hypertension. Conclusion: The study population had good knowledge about anemia, PIH and fair knowledge regarding GDM.